Comprehensive approaches to crisis management: Complex crises require effective coordination and political leadership - Claudia Major; Elisabeth Schöndorf (Stiftung Wissenschaft und Politik (SWP), 2011)
Today's crises bring together social, economic and political security dimensions. Managing them requires the concerted use of diplomatic, military, civilian, humanitarian and development aid instruments. This is what makes crisis management complex. Those involved are becoming more numerous, duties and responsibilities are becoming more diverse and commitments more drawn-out. To achieve successful outcomes, governments and other actors involved need to coordinate their aims, activities and instruments at the earliest possible stage and ensure these are tailored to need. This is what comprehensive approaches are all about. New concepts and structures should be introduced to guarantee the coordination and cooperation of those involved at national and international levels. In practice, however, such efforts often come to grief in identifying the various different problems and approaches to resolving them, as well as in resistance to reform and inadequate funding
Keywords: 320